Synthesis of Conjugated Rod-Coil Block Copolymers by RuPhos Pd-Catalyzed Suzuki-Miyaura Catalyst-Transfer Polycondensation: Initiation from Coil-Type Polymers - Choi, Hae Nam; Yang, Hee Seong; Chae, Ju Hyung; Choi, Tae Lim; Lee, In Hwan (Macromolecules, 2020)
A novel coil-first/grafting-from approach was developed for the synthesis of conjugated rod-coil block copolymers using RuPhos Pd-catalyzed Suzuki-Miyaura catalyst-transfer polycondensation (SCTP). First, aryl iodide end-functionalized polystyrene (PS) was prepared as a macroinitiator for SCTP via atom transfer radical polymerization (ATRP) followed by sequential end-group modifications, azidation, and click reactions. Then, RuPhos Pd-catalyzed SCTP using the PS macroinitiator was carried out in the presence of N-methyliminodiacetic acid boronate-containing 3-hexylthiophene monomer (M1), and this afforded well-defined PS-block-poly(3-hexylthiophene) with excellent control and high yield. The scope of this method was successfully expanded to include poly(methyl acrylate)-, poly(methyl methacrylate)-, and poly(ethylene oxide)-block-poly(3-hexylthiophene) with controlled molecular weight and low dispersity. Further, the combination of the conventional rod-first and newly developed coil-first approaches facilitated the straightforward synthesis of a unique ABC-type rod-coil-rod triblock copolymer that was limitedly accessible by other methods. We believe that this efficient and readily accessible synthetic platform would be highly useful for the preparation of novel conjugated rod-coil block copolymers that can be applied in optoelectronics, battery engineering, and chemical sensing.
Keywords: Catalyst transfers; Chemical sensing; Controlled molecular weight; End-group modification; Macroinitiators; Poly (3-hexylthiophene); Poly methyl acrylate; Rod-coil block copolymer